Determination of selected antibiotics in the Istanbul strait sediments by solid-phase extraction and high performance liquid chromatography - Okay, Oya S.; Li, Kuixiao; Yediler, Ayfer; Karacik, Burak (Informa UK Limited, 2012)
Surface sediments from 12 different locations of the Istanbul Strait and Marmara Sea, Turkey were analysed for five antibiotics belonging to two different groups of widely used pharmaceuticals, tetracyclines (TCs) and fluoroquinolones (FQs), by solid-phase extraction and high performance liquid chromatography. These two groups of antibiotics, mainly used to prevent or treat illness for humans as well as for animals, are frequently detected in the effluent of municipal sewage plants, in the aquatic environments and in soils after being spread by liquid manure. The results of analysis revealed that measured concentrations of individual antibiotics were significantly different depending on sampling location. Chlortetracycline (CTC) was not detected in any of the samples. High concentrations were mainly found in urbanized regions of the Strait. The concentrations of the two tetracyclines ranged from not detectable to 27.3 μg kg(-1) in freeze-dried marine sediments. Comparable results were obtained for the two fluoroquinolones with concentration levels from 1.3 μg kg(-1) up 34.1 μg kg(-1). This study is the first attempt to show the contamination degree of the Istanbul Strait sediments by emerging contaminants. Particular concern should be given concerning their potential side effects caused by the frequent consumption of mussels and fishes captured in the Istanbul Strait.
Keywords: Geologic Sediments; Turkey; Oceans and Seas; Solid Phase Extraction; Anti-Bacterial Agents; Tetracyclines; Environmental Pollutants; Chromatography, High Pressure Liquid; Environmental Monitoring; Fluoroquinolones